Can clinically relevant dose errors in patient anatomy be detected by gamma passing rate or modulation complexity score in volumetric-modulated arc therapy for intracranial tumors?. (3rd March 2017) - Ohira, Shingo; Ueda, Yoshihiro; Isono, Masaru; Masaoka, Akira; Hashimoto, Misaki; Miyazaki, Masayoshi; Takashina, Masaaki; Koizumi, Masahiko; Teshima, Teruki
Abstract: We investigated whether methods conventionally used to evaluate patient-specific QA in volumetric-modulated arc therapy (VMAT) for intracranial tumors detect clinically relevant dosimetric errors. VMAT plans with coplanar arcs were designed for 37 intracranial tumors. Dosimetric accuracy was validated by using a 3D array detector. Dose deviations between the measured and planned doses were evaluated by gamma analysis. In addition, modulation complexity score for VMAT (MCSv) for each plan was calculated. Three-dimensional dose distributions in patient anatomy were reconstructed using 3DVH software, and clinical deviations in dosimetric parameters between the 3DVH doses and planned doses were calculated. The gamma passing rate (GPR)/MCSv and the clinical dose deviation were evaluated using Pearson's correlation coefficient. Significant correlation ( P  < 0.05) between the clinical dose deviation and GPR was observed with both the 3%/3 mm and 2%/2 mm criteria in clinical target volume (D99 ), brain (D2 ), brainstem (D2 ) and chiasm (D2 ), albeit that the correlations were not 'strong' (0.38 < | r | < 0.54). The maximum dose deviations of brainstem were up to 4.9 Gy and 2.9 Gy for Dmax and D%, respectively in the case of high GPR (98.2% with 3%/3 mm criteria). Regarding MCSv, none of the evaluated organs showed a significant correlation with clinical dose deviation, and correlations were 'weak' or absent (0.01 < | r | < 0.21). The use of high GPR and MCSv values does not always detect dosimetric errors in a patient. Therefore, in-depth analysis with the DVH for patient-specific QA is considered to be preferable for guaranteeing safe dose delivery.